Property tables for thermal fluids engineering SI and U.S. customary units - Turns, Stephen R. (Cambridge University Press, 2006)
This booklet is an ideal supplement for any course in thermodynamics or the thermal fluid sciences and a handy reference for the practising engineer. The tables in the booklet complement and extend the property tables in the appendices to Stephen Turn's Thermodynamics: Concepts and Applications and Thermal-Fluid Sciences: An Integrated Approach. In addition to duplicating the SI tables in these books it extends the tables to cover US customary units as well. The booklet also contains property data for the refrigerant R-134a and properties of the atmosphere at high altitudes.